2019
DOI: 10.1177/2054358119858014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bisphosphonates on Bone Health in Adult Renal Transplant Patients: Beyond the First Year Posttransplant—A Systematic Review and Meta-Analysis

Abstract: Background: Bone mineral density (BMD) decreases postrenal transplantation. Evidence demonstrating the effects of bisphosphonates on BMD and fracture risk beyond 1-year posttransplant is sparse in existing literature, but remains essential to enhance clinical outcomes in this population. Objective: Our study aimed to systematically review and meta-analyze the current literature on the use of any bisphosphonate in the adult renal transplant population beyond the first year of renal transplant to determine its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
1
3
1
Order By: Relevance
“…Moreover, a recent meta-analysis study on RTR receiving bisphosphonates reported no statistical evidence for improvement in BMD in RTRs beyond the first year post-transplantation with the use of bisphosphonates. 18 Thus, the benefit of bisphosphonates may only be evident within 1 year of transplant, as shown in the current study. This is an important observation, as the protective effect may be limited to the time with the highest corticosteroid dosing and other pre-and post-transplant factors such as inflammation or bone disease.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Moreover, a recent meta-analysis study on RTR receiving bisphosphonates reported no statistical evidence for improvement in BMD in RTRs beyond the first year post-transplantation with the use of bisphosphonates. 18 Thus, the benefit of bisphosphonates may only be evident within 1 year of transplant, as shown in the current study. This is an important observation, as the protective effect may be limited to the time with the highest corticosteroid dosing and other pre-and post-transplant factors such as inflammation or bone disease.…”
Section: Discussionsupporting
confidence: 52%
“…The variability in the current study is attributed to the difference in study design, follow‐up treatment period, time of treatment initiation, and differences in patient characteristics. Moreover, a recent meta‐analysis study on RTR receiving bisphosphonates reported no statistical evidence for improvement in BMD in RTRs beyond the first year post‐transplantation with the use of bisphosphonates 18 . Thus, the benefit of bisphosphonates may only be evident within 1 year of transplant, as shown in the current study.…”
Section: Discussioncontrasting
confidence: 47%
“…However, according to previous research, the use of risedronate in patients with eGFR > 30 mL/min/1.73 m 2 did not aggravate renal impairment. 45 In patients with stage 1–4 CKD (52% of patients with eGFR ≤ 30 mL/min/1.73 m 2 ), risedronate retained BMD and reduced the incidence of lumbar spine fractures compared with placebo, with no more adverse renal events. 46 Alendronate did not increase renal adverse events in women with eGFR ≤ 45 mL/min/1.73 m 2 while it helped in improving lumbar spine and hip BMD.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several recent studies indicated that KT recipients have an above-average fracture rate, as they have fewer osteopenia. 3 In KT, the rate of fractures is higher in the first three years post KT by 34%; after that the general fracture risk is less and is comparable with dialysis patients. 4 Despite improving mineral metabolism, the fracture risk remains significant even ten years from KT.…”
Section: Introductionmentioning
confidence: 94%